A Case Study of Transformative Learning Experience Amongst Middle Managers - Ng, Chiew Sum (2008)
Work organisations in the current economic environment are facing unprecedented high energy costs, accelerated information communication technologies (ICT) and biotechnology changes. However, for most companies returns are increasing, with the application of knowledge that results in minimum utilisation of resources. Middle managers in these organisations are no longer able to manage work processes, market their products or services using the traditional command and control methods. They must refiame their perspectives to conceive new managerial roles based on resolving paradoxes and embracing a more entrepreneurial approach. The corporate managers must not only learn new managerial skills but they must also embark on transformative learning to improve their capabilities. Managers must question assumptions, formulate alternatives and continually reform their processes. The research approach adopted by this study is by using the qualitative case study method. Sampling of research sites and respondents were based on the criteria of access, industry type and the researcher's familiarity with the particular industry. This study adopted an unstructured interview method and twenty-five respondents were interviewed individually. The researcher conducted the interviews personally and the interview results were interpreted using an inductive analysis method.The main findings revealed that the middle managers' behavioural adaptive capabilities, insights and schemas were the results of their interaction with work situations and their interactions with colleagues, suppliers and customers, and owners. Learning was triggered not by disorienting &lemmas but by gradual accumulation of managerial insights and by the slow evolvement of new schemas spanning their working career. This study established the link between an individuals' transformative learning and their personal career advancements, work experience and external influence. The nature of transformative learning was found to be relational, as well as cognitive-rational. The findings contributed to the field of transformative learning by establishing the use of critical incidents/unstructured interviews in elucidating the transformative learning experiences of middle managers, and by creating dialogic context for managers to communicate their learning experiences. Theoretical contributions of this study included the level of transformative learning, cumulative layering of insights and true tests of transformative learning